2016
DOI: 10.4103/0970-9290.183126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental fluorosis among primary school children in association with different water fluoride levels in Mysore district, Karnataka

Abstract: A significantly positive correlation was found between CFI and water fluoride concentration in drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
2
11
1
3
Order By: Relevance
“…In the current study, 34.9% of the study participants had mild fluorosis, a similar finding was reported by Idon PI et al 28 where 32.1% participants reported mild fluorosis. A contrasting finding of 18.5% mild fluorosis was found in a study done by Sebastian ST et al 29 , which coincides with the findings by Chaudhry M et al 30 . Dental fluorosis is mainly because of the concentration of fluoride in drinking water which varies with geography, hence the reason for contrasting results.Tamil Nadu is one of the 19 states with high fluoride contamination in drinking water, varying from 1.0 -48 mg per litre 31 .…”
Section: Resultssupporting
confidence: 76%
“…In the current study, 34.9% of the study participants had mild fluorosis, a similar finding was reported by Idon PI et al 28 where 32.1% participants reported mild fluorosis. A contrasting finding of 18.5% mild fluorosis was found in a study done by Sebastian ST et al 29 , which coincides with the findings by Chaudhry M et al 30 . Dental fluorosis is mainly because of the concentration of fluoride in drinking water which varies with geography, hence the reason for contrasting results.Tamil Nadu is one of the 19 states with high fluoride contamination in drinking water, varying from 1.0 -48 mg per litre 31 .…”
Section: Resultssupporting
confidence: 76%
“…The prevalence of Dental fluorosis among school children in rural areas of Koppal district was 2279 (74.8%), which is very high compared to other studies done both within and outside India during different time periods 11,[13][14][15][16][17][18] and majority of them have used the same Dean's fluorosis to detect Dental Fluorosis. However, a couple of studies done in Rajasthan 19 and Karnataka 20 have found prevalence of Dental fluorosis in their studies comparable to the present study.…”
Section: Discussionmentioning
confidence: 83%
“…Minimum sample size calculated was 2166 with absolute precision of 3% and significance level of 0.05 and design effect of 2, taking 42% prevalence of Dental fluorosis in Karnataka 11 as per recent estimates. We included 3047 school children aged between 6 years to 12 years in the present study.…”
Section: Sample Sizementioning
confidence: 99%
“…Dental fluorosis is a disturbance in tooth formation caused by the excessive intake of fluoride during the formative period of dentition, and results in the mottling of dental polish, hard and fragile [13,14]. The most severe manifestation of fluorosis is bone damage which features osteosclerosis, ligament calcifications, and often osteoporosis, osteomalacia, or osteopenia [15,16].…”
Section: Introductionmentioning
confidence: 99%